(untitled) (Biological Sciences - PJSIR, 1998)
UV- Visible Absorption Spectroscopic Properties. Ultraviolet- Visible absorption spectroscopic data for dyes 1,2 and 3 are summarized in Table 2. Absorption maxima in various solvents are also given.